Estimasi Kesuburan Perairan Teluk Lampung berdasarkan Vertically Generalized Production Model (VGPM): Estimation of Lampung Bay Waters Fertility Based on Vertically Generalized Production Model (VGPM) - Rastina; Hartanto, Mochamad Tri; Febrianto, Muhammad Riza Hanief; Susanti, Santi; Lestari, Dea Fauzia; Prartono, Tri; Effendi, Irzal; Martinez, Stepahnie J.; Zaki, Nurul Hidayah Mat (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
Lampung Bay is an important water crossing in South Sumatra that is greatly influence by anthropogenic activities and oceanographic characteristics. This study characterized and estimated the spatial and temporal Primary Productivity (PP) in the three sections of the bay: head, middle, and mouth. The PP was modeled by using Sea Surface Temperature (SST), chlorophyll-a, Primary Productivity, and Photosynthetically Active Radiation (PAR) collected from remote sensing data and field measurements. Primary productivity was modeled with a Vertically Generalized Production Model (VGPM), and data validation was done using the Root Mean Square Error method. The distribution of PAR in Lampung Bay ranged from 35–52.50 E/m2/day. The distribution of SST ranged from 28.5–31.50°C. The highest distribution of chlorophyll-a was at the hHead of the bay with a range of 0.30-12 mg/m3. Correlation analysis shows that chlorophyll-a had the highest influence on PP (R2=0.99). While the middle and outer areas of the bay have a low average with values of 122.65 and 101.84 gC/m2/year. Our models show that there is high primary production at the Head of the bay, reaching eutrophic and mesotrophic levels. The middle and outer areas of the bay show productivity levels corresponding to mesotrophic and oligotrophic levels.